Rhodobacter azotoformans LPS (RAP99-LPS) Is a TLR4 Agonist That Inhibits Lung Metastasis and Enhances TLR3-Mediated Chemokine Expression - Murakami, Kaoru; Kamimura, Daisuke; Hasebe, Rie; Uchida, Mona; Abe, Nobuya; Yamamoto, Reiji; Jiang, Jing-Jing; Hidaka, Yasuhiro; Nakanishi, Yuko; Fujita, Shuzo; Toda, Yuki; Toda, Nobuhiro; et al. (Frontiers in Immunology, 2021)
The lipopolysaccharides (LPSs) of Rhodobacter are reported to be TLR4 antagonists. Accordingly, the extract of Rhodobacter azotoformans (RAP99) is used as a health supplement for humans and animals in Japan to regulate immune responses in vivo. We previously analyzed the LPS structure of RAP99 (RAP99-LPS) and found it is different from that of E. coli-LPS but similar to lipid A from Rhodobacter sphaeroides (RSLA), a known antagonist of TLR4, with both having three C14 fatty acyl groups, two C10 fatty acyl groups, and two phosphates. Here we show that RAP99-LPS has an immune stimulatory activity and acts as a TLR4 agonist. Pretreatment of RAP99-LPS suppressed E. coli-LPS-mediated weight loss, suggesting it is an antagonist against E. coli-LPS like other LPS isolated from Rhodobacter. However, injections of RAP99-LPS caused splenomegaly and increased immune cell numbers in C57BL/6 mice but not in C3H/HeJ mice, suggesting that RAP99-LPS stimulates immune cells via TLR4. Consistently, RAP99-LPS suppressed the lung metastasis of B16F1 tumor cells and enhanced the expression of TLR3-mediated chemokines. These results suggest that RAP99-LPS is a TLR4 agonist that enhances the activation status of the immune system to promote anti-viral and anti-tumor activity in vivo.